The spirituality and religiosity of people on hemodialysis treatment: integrative review (Research, Society and Development, 2022)
Objective: End-stage chronic kidney disease (ESRD) has a major impact on the quality of life of the individual with it. In this context, spirituality and religiosity are seen as resources that can help these people to deal with their illness. Therefore, this work starts from the following guiding question: “How do spirituality and religiosity influence the lives of people undergoing hemodialysis treatment? The objective was to identify evidence on how spirituality and religiosity can influence the life of end-stage renal patients on hemodialysis. Method: It consists of an integrative literature review, carried out by peers, in the following bases: PubMed, Web of Science, CINAHL, Science Direct, BVS, in February 2022, primary articles were adopted as inclusion criteria and secondary articles were excluded , following the method recommendations. Result: 994 records were identified, and 987 studies irrelevant to the review, duplicates, editorials and congress abstracts were discarded, leaving seven articles. After reading in full, five articles were selected for review. Conclusion: The benefits of spirituality and religiosity in coping with the diversities encountered by chronic renal patients on hemodialysis during their treatment were present in this study, however, it highlighted the need to add new knowledge on the subject in order to improve the care of the individual.